Analisis Penyebab Rendahnya Asupan Nutrisi Susu Sebagai Pendukung Gaya Hidup Sehat Pada Generasi Z - Hidayat, Nadia; Najwa, Rafika; Syakira, Rahma; Rozak, Rama Wijaya Abdul; Ramadhani, Tsabitha Nafisa; Sugiarti, Yatti; Dzulhijjah, Zihan Nur (Universitas Gajah Putih, 2024)
Indonesia has the advantage of developing the agricultural industry,cattle farming is one of the growing fields of animal husbandry in Indonesia. The most product from cattle farming is milk. In 2020, according to BPS ( Central Bureau of Statistics ), Indonesian people consumed milk still around 16.27 liters per capita per year. Dairy products released by the livestock industry and the people who consume them are still relatively low. Therefore,the purpose of this study is to analyze the causes of the low nutritional value of milk as a supporter of a healthy lifestyle in generation Z. The data were collected using a questionnaire and alnalyzed with a qualitative approach, as well as distributing questionnaires online using Google Froms and obtained 112 Generation Z respondents. Nutritional education may be a factor influencing milk consumption in Generation Z. The benefits and milk allergy. The result of the analysis prove that education about the nutritional value of milk, the price of milk and milk allergies affect Generation Z’milk consumption. While the factor that has no effect is milk variants. From the results of the analysis,it can be concluded that the internal factors that influence are individual habits in consuming milk. While the external factor that influences is the selling price of milk.